Effect of word-focused activity on reading and learning of L2 vocabulary: A self-paced reading study - Hyeonah Kang; Janet Nicol (Vocabulary Learning and Instruction)
Many researchers suggest that text-reading should be followed by an activity that requires learners to use the new vocabulary, before they read the text again (e.g., De Vos et al., 2019; Nguyen & Boers, 2019). The first article of this dissertation also demonstrated the benefits of post-reading word-focused activity on vocabulary learning in an environment when there is no instructor support, particularly for L2 high-intermediate learners compared to monolingual native speakers. But how exactly does this help? Does the post-reading activity make learners aware of gaps in their knowledge of the new vocabulary? If it does, this may lead them to pay more attention to those words in a subsequent reading, ultimately resulting in vocabulary uptake. To address this question, the current study employed a self-paced reading task to examine the reading behaviors during the re-reading of a text following a word-focused activity. Results showed that engaging with target items during the word-focused activity facilitated memory retention of their meanings. However, this word-focused activity did not result in increased attention to reading target items during the rereading task.